PSYCHOLOGICAL AND PEDAGOGICAL BASIS OF THE DEVELOPMENT OF THE CREATIVE ACTIVITY OF THE FUTURE TEACHER IN LEARNING A FOREIGN LANGUAGE - Пащенко, М.І.; Левчук, О. (SWorldJournal, 2024)
The article presents a psycho-pedagogical analysis of the creative educational activity of education seekers. The abilities of students, which are formed in creative activities, have been determined. The psychological and pedagogical conditions for the de